Epitaxial Grown Carbon Nanotubes Reinforced Pyrocarbon Matrix in C/C Composites with Improved Mechanical Properties - Ningkun Liu (MDPI AG, 2021)
In order to achieve the highly efficient preparation of high-performance carbon/carbon (C/C) composites, epitaxial grown carbon nanotubes (CNTs) and a pyrocarbon matrix were simultaneously synthesized to fabricate CNT-reinforced C/C composites (CC/C composites). With precise control of the temperature gradient, CNTs and the pyrocarbon matrix could grow synchronously within a 2D needle-punched carbon fiber preform. Surprisingly, the CNTs remained intact within the pyrocarbon matrix at the nano-level, and the CNT-reinforced nano-pyrocarbon matrix was compact, with virtually no gaps and pores, which were tightly connected with the carbon fibers without cracks. Based on the results of Raman analysis, there is less residual stress in the CNT-reinforced pyrocarbon matrix and carbon fibers, and less of a mismatch between the coefficient and thermal expansion. Additionally, CC/C composites fabricated by this method could achieve a low density, open porosity with a large size, and improved mechanical properties. More importantly, our work provides a rational design strategy for the highly efficient preparation and structural design of high-performance CNT-einforced C/C composites.